(untitled) (American Journal of Technology and Applied Sciences, 2023)
An analysis of the parameters of the blood hemostasis system in patients with chronic obstructive pulmonary disease was performed. The data presented highlight the significant pathogenetic significance of changes in hemostasis in patients with chronic obstructive pulmonary disease, which requires the search for new methods of pathogenetic therapy based on anticoagulant effects.